2016
DOI: 10.1007/s40195-016-0405-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Multi-pass Friction Stir Processing on Microstructure and Mechanical Properties of Die Cast Al–7Si–3Cu Aluminum Alloy

Abstract: The influence of overlap multi-pass friction stir processing on the microstructure and the mechanical properties, in particular, strength, ductility and hardness of die cast Al-7Si-3Cu aluminum alloy was investigated. It was observed that increase in the number of overlap passes friction stir processing resulted in significant refinement and redistribution of aluminum silicon eutectic phase and elimination of casting porosities. The microstructural refinement by the friction stir processing not only increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 27 publications
(43 reference statements)
2
8
0
Order By: Relevance
“…Baruch et al 11 investigated the effect of multi-pass FSP on the microstructure and mechanical properties of the AS7U3G cast alloy. They reported that the hardness of the FSP specimens was lower than that of the as-cast alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Baruch et al 11 investigated the effect of multi-pass FSP on the microstructure and mechanical properties of the AS7U3G cast alloy. They reported that the hardness of the FSP specimens was lower than that of the as-cast alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Both strength and ductility were enhanced as the grain size reduces. [10][11][12] For the refinement of primary Si, various microstructural refinement techniques were used by the researchers in the as-cast Al-Si alloys, which includes melt modification, [13][14][15][16][17][18] spray forming, 19,20 friction stir processing (FSP), 2,21,22 and squeeze casting. 23 After examining the research papers, the effect of microstructural refinement due to a reduction in primary silicon particles on tensile properties is tabulated in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The refined grain of surface composites enhanced corrosion resistance, hardness and wear resistance properties. It was reported that ultrafine structure formed surrounding the rotating tool pin due to the deformation field generated for this reason [60][61][62]. The FSP pass affects the grain structure of the surface composite.…”
Section: Effects Of Number Of Fsp Passesmentioning
confidence: 99%